Spatial patterns of spring meroplankton along environmental gradients in a sub-Arctic fjord - Michelsen, Helena Kling; Nilssen, Einar Magnus; Pedersen, Torstein; Reigstad, Marit; Svensen, Camilla (Inter-Research, 2017)
Source at https://doi.org/10.3354/ab00686 . The spatial patterns in abundance and composition of benthic invertebrate larvae (meroplankton), the correlation between these patterns and environmental variables (temperature, salinity and chl a) and the relative abundance of meroplankton in the mesozooplankton community were investigated in the sub-Arctic Porsangerfjord, Norway (70° N). Zooplankton samples and CTD-profiles were collected at 17 stations along the fjord in April 2013. A total of 32 morphologically different larval types belonging to 8 phyla were identified. Meroplankton were found at all stations, and their community and abundance differed significantly along the fjord. Meroplankton abundance in the inner and outer parts of the fjord was low and was dominated by Gastropoda and Echinodermata. The greatest numbers were recorded in shallow bays and the middle part of the fjord where Cirripedia and Polychaeta were dominant. Meroplankton contributed significantly to the mesozooplankton community in the bays (30 to 90%) and mid-fjord (13 to 48%) areas. These changes in community structure were attributed to spatial gradients in environmental variables such as chl a, salinity and temperature. The different communities suggested a seasonal succession in reproductive events from the fjord mouth toward the head. Considering that spring is an important season for reproduction in pelagic organisms, meroplankton may play a role in the pelagic ecosystem of high-latitude fjords as grazers and prey. Furthermore, the spatial dynamics and reproductive timing of benthic and holoplanktonic organisms are sensitive to local hydrographical features, illustrating their sensitivity to changing environments.